The antiulcer effect of Croton cajucara Benth in normoproteic and malnourished rats - De Paula, Ana Claudia B.; Gracioso, Juliano S. [UNESP]; Toma, Walber; Hiruma-Lima, Clélia Akiko [UNESP]; Carneiro, Everardo M.; Souza Brito, Alba R. M. (Elsevier Gmbh, Urban & Fischer Verlag, 2008)
The aim of the present study is to investigate the antiulcerogenic effects of the essential oil (EO) of Croton cajucara Benth in rats fed with a normal protein (NP) and low-protein diet (MN).NP and MN rats were treated with the essential oil for 15 days after chronic ulceration was induced. The EO accelerated healing of acetic acid-induced gastric lesions in NP and MN rats (p < 0.05). In a similar experiment on chronic ulceration, Epidermal Growth Factor (EGF) mRNA expression increased in NP rats but not in MN rats.In assays of acute antiulcerogenic activity, C. cajucara increased somatostatin plasma levels and decreased gastrin plasma levels in both animal groups. The EO significantly prevented ethanol-induced gastric ulcers in NP and MN rats (P < 0.001).Histological examination showed initial regeneration, formation of inflammatory infiltrate and anglogenesis in the epithelium surface of acetic acid-induced ulcers in NP and MN rats. C. cajucara prevented gastric lesions in both animal groups when ethanol methodology was used. We concluded that the EO showed an antiulcerogenic activity mediated by increased somatostatin secretion and EGF mRNA expression. (C) 2008 Elsevier GmbH. All rights reserved.
Keywords: Malnourished rats; Essential oil; Croton cajucara; Medicinal plants; Gastric ulcer